Le séminaire de recherche : un lieu pour structurer la formation à l'enseignement autour de l'articulation théorie et pratique - Sylvain Doussot; Anne Vézier (Nantes Université, 2016)
In a professional and academic training as in a teachers training, an introduction to research practices is to be discussed. We try to do so on the basis of a research seminar in didactics (and the case of one student in particular) enforced in a master in teaching history and geography. Our theoretical frame ("problematization") shows how such a seminar can help junior teachers building knowledge about teaching/learning situations if based on theoretical and empirical conditions. What is at stake here is professional training, but teaching history is not just any profession: it has close links to research practices.